Reported Sildenafil Side Effects in Pediatric Pulmonary Hypertension Patients - Siehr, Stephanie L.; McCarthy, Elisa K.; Ogawa, Michelle T.; Feinstein, Jeffrey A. (Frontiers in Pediatrics, 2015)
Background: Sildenafil, a phosphodiestase type 5 inhibitor, was approved in 2005 for the treatment of pulmonary arterial hypertension (PAH) in adults and is commonly used off-label for pediatric patients. Little is known, however, about sildenafil’s side effects in this population. Methods: Single institution, longitudinal survey-based study performed in an outpatient pediatric cardiology clinic. Pediatric patients on sildenafil [alone or in combination with other pulmonary hypertension (PH) therapies] completed questionnaires regarding frequency of vascular, gastrointestinal, neurologic, and hematologic side effects. Results: Between January 2011 and May 2014, 66 pediatric patients with PH on sildenafil filled out 214 surveys, 32 patients (96 surveys) on monotherapy, and 43 patients (118 surveys) on sildenafil plus an endothelin receptor antagonist (ERA) (bosentan or ambrisentan) and/or a prostacyclin (epoprostenol or treprostinil). Overall, 30% of respondents identified at least one side effect. For all patients on sildenafil, incidence of side effects by system was 37% gastrointestinal, 35% vascular, and 22% neurologic. For patients on sildenafil monotherapy, incidence of side effects by system was 24% gastrointestinal, 21% vascular, and 18% neurologic compared to patients on combination therapy who reported an incidence of 48% gastrointestinal, 45% vascular, and 25% neurologic. Conclusion: Incidence of vascular, gastrointestinal, and neurologic side effect in pediatric patients on sildenafil therapy for PAH was 30%. Side effects were more common in patients on combination therapy with an ERA and/or prostacyclin than in patients on sildenafil monotherapy.